The Influence of Price, Product Quality and E-Wom on Customer Satisfaction and Repurchase Intention: Study on Moslem Daily Wear (Hijab Buttonscarves Products) - Raniyah Diva Rosalbah; Rachma Rizqina Mardhotillah (Journal of Halal Research, Policy, and Industry, 2023)
Indonesia is a country with the majority of Muslims in the world. One of the fastest changing trends in Muslim fashion products is hijab. This fact is intended for companies so that they can carry out their business processes in order to retain potential old consumers and get new consumers. This study aims to analyze the effect of price, product quality, and E- WOM on customer satisfaction and repurchase intention. This research method uses quantitative methods with purposive sampling techniques. The questionnaire was distributed online via google form which was distributed to 200 respondents within 1 week. The analysis in this study used Partial Least Square (PLS). The results in this study are that there is a significant influence between price and product quality on customer satisfaction. price and customer satisfaction have a significant influence on repurchase interest. however, this study found that E-WOM has an insignificant effect on customer satisfaction and repurchase interest, and product quality has an insignificant effect on repurchase interest